Antidiabetic treatment with gliptins: focus on cardiovascular effects and outcomes. Issue 1 (December 2015) - Fisman, Enrique; Tenenbaum, Alexander
Abstract The traditional oral pharmacological therapy for type 2 diabetes mellitus (T2DM) has been based on the prescription of metformin, a biguanide, as first line antihyperglycemic agent world over. It has been demonstrated that after 3 years of treatment, approximately 50 % of diabetic patients could achieve acceptable glucose levels with monotherapy; but by 9 years this had declined to only 25 %. Therefore, the implementation of a combined pharmacological therapy acting via different pathways becomes necessary, and its combination with a compound of the sulfonylurea group was along decades the most frequently employed prescription in routine clinical practice. Meglitinides, glitazones and alpha-glucosidase inhibitors were subsequently developed, but the five mentioned groups of oral antihyperglycemic agents are associated with variable degrees of undesirable or even severe cardiovascular events. The gliptins—also called dipeptidyl peptidase 4 (DPP4) inhibitors—are an additional group of antidiabetic compounds with increasing clinical use. We review the status of the gliptins with emphasis on their capabilities to positively or negatively affect the cardiovascular system, and their potential involvement in major adverse cardiovascular events (MACE). Alogliptin, anagliptin, linagliptin, saxagliptin, sitagliptin, teneligliptin and vildagliptin are the compounds currently in clinical use. Regardless differences in chemical structure and metabolic pathways, gliptins as a group exert favorable changes in experimental models. These changes, as an almost general rule, include improved endothelial function, reduction of inflammatory markers, oxidative stress ischemia/reperfusion injury and atherogenesis. In addition, increased adiponectin levels and modest decreases in lipidemia and blood pressure were reported. In clinical settings, several trials—notably the longer one, employing sitagliptin, with a mean follow-up period of 3 years—did not show an increased risk for ischemic events. Anyway, it should be emphasized that the encouraging results from basic science were not yet translated into clinical evidence, probably due the multiple and pleiotropic enzymatic effects of DPP4 inhibition. Moreover, when employing saxagliptin, while the drug was not associated with an augmented risk for ischemic events, it should be pinpointed that the rate of hospitalization for heart failure was significantly increased. Gliptins as a group constitute a widely accepted therapy for the management of T2DM, usually as a second-line medication. Nonetheless, for the time being, a definite relationship between gliptins treatment and improved cardiovascular outcomes remains uncertain and needs yet to be proven.